Factors affecting carbon nanotube fillers towards enhancement of thermal conductivity in polymer nanocomposites: A review. (November 2017) - Namasivayam, Muthuraman; Shapter, Joe
Thermally conductive polymer composites have opened up new possibilities in various applications including solar cells, power generators, electronics, biomedical applications, etc. Polymer matrices have some interesting advantages to offer such as being lightweight, cost effective, corrosion resistant, and many more. However, the thermal conductivity of a polymer matrix is relatively low for some commercial applications. Recent research has focused on enhancing the thermal conductivity of polymer composites through addition of nanofillers such as nanotubes, graphite, carbon fibers, etc. Among these possibilities, carbon nanotubes are considered to be promising candidates due to their unusually high thermal conductivity. This article discusses the properties of nanotube fillers that should be taken into account in order to fabricate a thermally conductive polymer nanocomposite and reviews the status of research in terms of thermal conductivity and nanotubes.